DESIGN PLANNING OF WATER TREATMENT PLANT (WTP) II IN THE SUMMARECON BANDUNG AREA - Afiyanti Putri, Regia
Summarecon Bandung, as the first integrated city development in Bandung City, faces challenges in providing clean water independently due to the absence of a water distribution network from PDAM Bandung in the Gedebage District. To reduce reliance on groundwater, Summarecon Bandung plans the construction of a Water Treatment Plant (WTP) with a design capacity of 120 LPS, to be built in stages. Currently, a WTP with a capacity of 20 LPS is operational, serving 1,058 household connections (SR). Based on projected water demand until 2045, an increase in capacity to 120 LPS is required to serve 5,883 SR. Therefore, WTP II with a capacity of 100 LPS is planned to be constructed in two stages, each with 50 LPS, with the first stage expected to become operational in 2026 and the second in 2035. The design of WTP II begins with projecting the number of residents and analyzing the raw water quality from lakes used as the water source. Parameters such as turbidity, color, fecal coliform, and total coliform do not meet the drinking water quality standards outlined in the Ministry of Health Regulation No. 2 of 2023, influencing the selection of treatment units. Three design alternatives are developed using the matrix models of Kawamura, JICA, and SNI, and are selected using the SAW method. The chosen alternative includes hydraulic-type coagulation with PAC coagulant, flocculation with vertical baffle channels, sedimentation with plate settlers, rapid sand filtration, and disinfection with chlorine. With the available land area of 7,063.94 m², the total land required for both stages is 1,546 m². The total investment required is Rp 6,001,428,581 with operational costs amounting to Rp 18,555,074,327 until 2045. Based on the economic analysis, with NPV > 0, the project is deemed economically feasible.